Perlindungan Hukum Penumpang Pesawat Terbang atas Keterlambatan Maskapai Menurut Peraturan Menteri Perhubungan RI Nomor 89 Tahun 2015 dan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Rindiantika, Vista; Djatmiko, Sugeng (HUMANIORUM, 2025)
Air transportation has now developed rapidly so that many new airline companies are providing air transportation services and more and more people are using airplane services. In this case, there is still a lot of attention needed from the airline related to passenger rights which until now are still not considered in the schedule which results in flight delays for passengers. In this study, the researcher uses a normative juridical method by examining Law Number 1 of 2009, Regulation of the Minister of Transportation Number 89 of 2015 and Law Number 8 of 1999 and other legal journals. The researcher in this case carried out a descriptive analysis approach that aimed to examine related to legal protection for aviation consumers who experienced flight delays. The form of legal remedies taken in this dispute can be carried out inside or outside the court so that the liability of the airline can apply to the maximum. Responsibility in this case adopts the principle of presumption of liability.